Pendular Nystagmus Presenting in Usher Syndrome Type I: A Case Report - Bogle, Jamie M.; Zapala, David A. (Journal of the American Academy of Audiology, 2024)
Background We describe a 42-year-old patient with reported “shaking” vision referred due to concerns of possible vestibular system dysfunction. The patient has known history of Usher syndrome type I, bilateral cochlear implants, and severe vision impairment.Purpose This case describes an unusual nystagmus previously only reported in individuals with central demyelinating disorders, significant light deprivation, or in congenital/early-onset visual pathway impairment.Research Design Case study.Data Collection and Analysis Retrospective chart review of vestibular function.Results Vestibular function was likely absent in this case. There was no evidence of vestibular (jerk) nystagmus for sinusoidal harmonic acceleration stimuli or repeatable responses for cervical vestibular evoked myogenic potentials. Significant pendular low-amplitude high-frequency oscillations of approximately 6 Hz were present for horizontal and vertical tracings throughout testing.Conclusion Nystagmus may not always be associated with vestibular system impairment. In this case, the patient's reported “shaking” vision was attributed to pendular low-amplitude high-frequency nystagmus and hypothesized to relate to long-standing significant vision impairment. This presentation is unusual in adults and has historically been associated with individuals with significant central pathology or in those with long duration light deprivation.
Keywords: vestibular system; pendular nystagmus; Usher syndrome